2020
DOI: 10.1002/lno.11395
|View full text |Cite
|
Sign up to set email alerts
|

Climate and geographic adaptation drive latitudinal clines in biomass of a widespread saltmarsh plant in its native and introduced ranges

Abstract: Introduced plants provide a unique opportunity to examine how plants respond through plasticity and adaptation to changing climates. We compared plants of Spartina alterniflora from the native (United States, 27–43°N) and introduced (China, 19–40°N) ranges. In the field and greenhouse, aboveground productivity of Chinese plants was greater than that of North American plants. Aboveground biomass in the field declined with increasing latitude in the native range, a pattern that persisted in the greenhouse, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 66 publications
2
29
0
Order By: Relevance
“…S. alterniflora in China also retains similar plastic responses to elevation (Peng et al , ; Zhu et al , ). In the USA, sampling S. alterniflora in the ‘midmarsh’ produced similar latitudinal patterns as we have described here for samples collected from the low marsh (Kirwan et al , ; Liu et al , ), so we hypothesised that, if we had included midmarsh sampling in this paper, contrasts between the native and exotic ranges would have been similar to those that we documented in the low marsh. Testing this hypothesis is a matter for future studies.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…S. alterniflora in China also retains similar plastic responses to elevation (Peng et al , ; Zhu et al , ). In the USA, sampling S. alterniflora in the ‘midmarsh’ produced similar latitudinal patterns as we have described here for samples collected from the low marsh (Kirwan et al , ; Liu et al , ), so we hypothesised that, if we had included midmarsh sampling in this paper, contrasts between the native and exotic ranges would have been similar to those that we documented in the low marsh. Testing this hypothesis is a matter for future studies.…”
Section: Discussionsupporting
confidence: 69%
“…Populations of S. alterniflora in China are more productive than the native populations in North America (Qing et al , ; Shang et al , ), but geographic variation in standing biomass appears to be driven by the same abiotic factors in the native versus introduced range (Liu et al , ). It is unclear to what extent the greater productivity in the introduced range is due to the specific source sites of the invasion (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicates that the invasion magnitude of S. alterniflora on native mangroves increased with increasing latitude, suggesting the mangrove community may be more susceptible to invasion at higher than at lower latitudes. This response is consistent with biogeographical patterns of their climatic niche, and agrees with previous study which indicated the aboveground biomass of S. alterniflora increases with latitude in Southern China (Liu et al, 2020). In low latitudes, climate conditions are suitable for survival and dispersal of freeze-sensitive mangroves, enhancing their competition on habitat niche with invasive salt marsh (Cavanaugh et al, 2019).…”
Section: Latitudinal Trends In Mangroves and S Alterniflorasupporting
confidence: 92%
“…Cross-bred genotypes spread rapidly through the temperate region of China in the 1980s, and dispersed into lower-latitude subtropical and tropical regions in the following decades (An et al 2007. Within the introduced range, S. alterniflora plants vary greatly in vegetative traits and seed set, with geographic variation in vegetative traits largely caused by phenotypic plasticity, and geographic variation in seed set largely caused by rapid evolution in the new environment (Liu et al 2016, Qiao et al 2019, Liu et al 2020a.…”
Section: Introductionmentioning
confidence: 99%